Relationships between student satisfaction and assessment grades in a first-year engineering unit - Dong, Yu; Lucey, Anthony (Murdoch University, 2013)
Monitoring the quality of teaching and learning by universities relies primarily upon a combination of feedback from formal student-evaluation surveys and the long-established measure of student-cohort performance in unit assessments. This study explores major factors that might affect the data provided by these two measures and seeks to identify potential relationships between assessment performance and each of student satisfaction and students’ engineering discipline interests. Enabling this study is a large data-set obtained over the last four years from the teaching of a first-year Engineering Mechanics unit delivered twice per year to approximately 350 students in each semester from all engineering and some of multi-science disciplines. Over these years, this unit has largely remained stable in terms of unit learning outcomes, syllabus, delivery methods and teaching staff, thereby permitting potentially robust conclusions to be drawn from analyses of the data-set. By interrogating this data-set, three questions are addressed in this paper, namely (i) Is there a correlation between academic performance and student satisfaction with the unit, (ii) Did a change in assessment weighting affect students’ overall performance, and (iii) Does student interest, as reflected by their engineering-oriented discipline choice, affect their overall assessment outcomes. The investigations presented in this paper are preliminary, focusing on four-semester studies in 2010 and 2011, adopting a broad-brush approach, in order to provide the direction to more refined and rigorous lines of enquiry using the same data to determine the efficacy of present monitoring systems for teaching and learning.The initial results show that student feedback is correlated well to their assessment performance provided that cultural bias is removed. Overall, the influence on performance of changing the assessment weighting appears to be minimal and does the students’ engineering-discipline interests.